2006
DOI: 10.1179/136485906x118477
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of ciprofloxacin on the in-vitro activity of chloroquine against a clinical isolate ofPlasmodium falciparum

Abstract: As chloroquine and ciprofloxacin each possess substantial inhibitory activity against the schizonts of Plasmodium falciparum, it seems possible that a combination of the two drugs may be clinically useful. The effects on the erythrocytic stages of P. falciparum of combined treatment with chloroquine and ciprofloxacin were therefore evaluated in vitro, using the World Health Organization's standardized micro test. When used alone, the median inhibitory concentration (IC(50)) of chloroquine against the schizonts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The interaction was demonstrated by a significant reduction in parasitemia and enhanced survival rate of the animals (80%) in the group of animals treated with the combination of CQ plus 160 mg/kg body weight CFX. Our results support previous reports describing beneficial interaction between CFX and CQ in vitro (Kazzim et al 2006) although results from our study show a dose dependent interaction between the two compounds in the combination. Combination of CQ with lower doses of ciprofloxacin was not beneficial and this finding is consistent with reports from Salmon and colleagues (Salmon et al 1990).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The interaction was demonstrated by a significant reduction in parasitemia and enhanced survival rate of the animals (80%) in the group of animals treated with the combination of CQ plus 160 mg/kg body weight CFX. Our results support previous reports describing beneficial interaction between CFX and CQ in vitro (Kazzim et al 2006) although results from our study show a dose dependent interaction between the two compounds in the combination. Combination of CQ with lower doses of ciprofloxacin was not beneficial and this finding is consistent with reports from Salmon and colleagues (Salmon et al 1990).…”
Section: Discussionsupporting
confidence: 92%
“…However they may be considered as part of combination therapy when administered with a rapidly acting antimalarial drug (Pradines et al 2001). Mutual enhancement of antimalarial activity during combination of chloroquine and ciprofloxacin against Plasmodium falciparum has been reported in vitro (Kazzim et al 2006). The interaction between both drugs was additive indicating that the combination may be potentially useful in the management of falciparum malaria.…”
Section: Introductionmentioning
confidence: 99%
“…(4)) (IC 50 = 10.4 M) [92]. In vitro studies showed additive effects upon combination of ciprofloxacin with chloroquine [94], primaquine, mefloquine or artesunate [95,96]. Enhanced activity owing to the combination of mefloquine or artesunate with ciprofloxacin was confirmed in vivo in P. berghei infected mice [96].…”
Section: Quinolonesmentioning
confidence: 85%
“…Pairwise comparison of the 492 active compounds identified 1,250 pairs that were negatively correlated, with CC ranging from −0.26 to -0.90 (Table S5). In particular, 43 compounds were negatively correlated with CQ, including ciprofloxacin and clindamycin, each of which has been reported to have antimalarial activity alone (26, 27). The combination of clindamycin and CQ (CC = −0.27) substantially improves patient cure rate as compared with CQ alone (94% compared to 32%) (26), and ciprofloxacin (CC = −0.30) significantly enhances CQ activity in vitro (27).…”
Section: Compounds With Correlated Responses and Response Signature Gmentioning
confidence: 99%